(untitled) (International Journal of Engineering and Computer Science, 2017)
Network coding is a process where an intermediate node encodes incoming packets before forwarding. In existing system, they decouple the routing and scheduling components of the algorithm by designing a probabilistic routing table that is used to route packets to perdestination queues. The back-pressure algorithm, while being throughput-optimal, is not useful in practice for adaptive routing since the delay performance can be really bad. However, using this algorithm will lead to deadlock, power consumption and less security. We proposed a system that implements the novel HOP VOTE scheme along with tag based authentication scheme for effective pollution attack detection recovery and blocking. This allows a node to verify if it’s received packet belong to specific rule criteria, even if the encrypted key is expanding over a time. Based on the id and tag creation the data will be routed. Using tag encoding scheme, the communication overhead can be routed. It is fast and reliable. Further, it improves security, throughput and efficiency of the system.